2021
DOI: 10.1002/jcb.29890
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional regulator Zfat is essential for maintenance and differentiation of the adipocytes

Abstract: Adipocytes play crucial roles in the control of whole‐body energy homeostasis. Differentiation and functions of the adipocytes are regulated by various transcription factors. Zfat (zinc‐finger protein with AT‐hook) is a transcriptional regulator that controls messenger RNA expression of specific genes through binding to their transcription start sites. Here we report important roles of Zfat in the adipocytes. We establish inducible Zfat‐knockout (Zfat iKO) mice where treatment with tamoxifen causes a marked re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The reduced expression of PSMC3 may contribute to the observed decrease in C/EBPα expression and TG levels in ZFAT-depleted adipocytes. 23 Significantly, the expression trends of COL5A2 and PSMC3 in the IMF-H and IMF-L groups observed in the present study are consistent with the aforementioned observations.…”
Section: Integrative Analysis Of Transcriptome and Proteome To Obtain...supporting
confidence: 92%
“…The reduced expression of PSMC3 may contribute to the observed decrease in C/EBPα expression and TG levels in ZFAT-depleted adipocytes. 23 Significantly, the expression trends of COL5A2 and PSMC3 in the IMF-H and IMF-L groups observed in the present study are consistent with the aforementioned observations.…”
Section: Integrative Analysis Of Transcriptome and Proteome To Obtain...supporting
confidence: 92%
“…The immunoblotting procedure was performed as previously described (19,37,42) using antibodies detailed in the Supplemental Table S3. Co-immunoprecipitation (Co-IP) was performed as previously described (43).…”
Section: Immunoblotting and Co-immunoprecipitationmentioning
confidence: 99%
“…The ZFAT genes have been identified in vertebrates with highly conserved amino acid sequences ( 14 ), suggesting their crucial role in physiological processes. Indeed, we have previously demonstrated that ZFAT is essential for embryonic development ( 15 ) and the homeostasis of T cells ( 16 , 17 , 18 ) and adipocytes ( 19 ). Recently, we reported that ZFAT plays an important role in the centromeric ncRNA transcription in human cells ( 20 ).…”
mentioning
confidence: 99%
“…However, there is limited research on the regulation of adipogenesis by RAD51AP1 . Among this research, RAD51AP1 was found in prenatal testosterone-induced visceral adipose tissue of female sheep and was highly expressed in the adipose-derived stem cells, which may be involved in lipid metabolism processes [ 48 , 49 ]. In our research, RAD51AP1 was a direct miR-383-5p target.…”
Section: Discussionmentioning
confidence: 99%